2020
DOI: 10.1177/0956462420945940
|View full text |Cite
|
Sign up to set email alerts
|

Sex-seeking mobile application use and risk behavior among men who have sex with men in Brazil

Abstract: This is a cross-sectional study based on an open web survey with the primary objective to assess associations between the use of apps for seeking sex partners and vulnerabilities related to human immunodeficiency virus (HIV) acquisition among men who have sex with men (MSM) in Brazil. Participants were recruited to the study through ads posted in social media such as Twitter, Facebook, and WhatsApp. Consenting respondents completed a questionnaire on demographics, history of sexually transmitted infections (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…A previous study in Vietnam among MSM showed that traveling alone and having a university schooling level was associated with casual sex [ 32 ]. In addition, the use of sex-seeking applicatives and recreational drugs in parties is related to an increase in risk to HIV among MSM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Vietnam among MSM showed that traveling alone and having a university schooling level was associated with casual sex [ 32 ]. In addition, the use of sex-seeking applicatives and recreational drugs in parties is related to an increase in risk to HIV among MSM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on apps use by MSM is conducted worldwide. Examples of this include studies from Australia [37], Brazil [38,39]; Canada [40], China [41][42][43][44][45][46][47], Ecuador [48,49], England [50], Japan [51], the Netherlands [52], the Philippines [53] and Spain [54,55]. Most of these studies explored topics such as users' experiences connecting with others through apps, engaging in high-risk behaviors, and using apps for obtaining sexual health and HIV prevention information, as well as the opportunities provided for promoting HIV testing and linkage to HIV treatment via apps to users.…”
Section: Plos Onementioning
confidence: 99%
“…(8) Os estudos brasileiros que incluem as minorias sexuais usuárias de aplicativos de encontros estão focados, particularmente, em homens que fazem sexo com homens (HSH). (9)(10)(11) Entretanto, o entendimento sobre as circunstâncias que levam ao comportamento sexual de risco entre jovens brasileiros, universitários e usuários desses aplicativos é escasso. (12) Essa abordagem é necessária, uma vez que o uso de tecnologia móvel é praticamente universal entre acadêmicos.…”
Section: Introductionunclassified